Pakistaniat and Fall of Dhaka - Nazir, Saba; Khan, Shaista Hameed (sourcecoder, 2024)
This paper examines the role of Pakistaniat, an ideology that emphasizes a unified Pakistani identity, in the events leading up to the Fall of Dhaka in 1971. The Fall of Dhaka marked the surrender of Pakistani forces to the Indian military and the subsequent independence of East Pakistan, now Bangladesh. Through a historical and political analysis, this paper argues that the imposition of Pakistaniat on East Pakistan contributed to the marginalization of Bengali identity and culture, ultimately leading to the demand for independence. The paper also explores how the military and political establishment’s insistence on a unified Pakistani identity fueled the conflict and ultimately led to the downfall of East Pakistan. This research provides new insights into the complex relationship between identity, politics, and conflict in the region.